1994
DOI: 10.1038/369571a0
|View full text |Cite
|
Sign up to set email alerts
|

c-Mpl ligand is a humoral regulator of megakaryocytopoiesis

Abstract: Megakaryocytopoiesis is the cellular developmental process that leads to platelet production. At least two humoral growth factors may be necessary for megakaryocyte proliferation and maturation. One is a megakaryocyte-colony stimulating factor (MK-CSF) which induces the proliferation and differentiation of megakaryocyte progenitors, and the second, thrombopoietin, is a megakaryocyte maturation factor. Neither of these factors has been fully characterized. The proto-oncogene c-mpl, an orphan member of the haema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
330
0
2

Year Published

1995
1995
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(339 citation statements)
references
References 17 publications
7
330
0
2
Order By: Relevance
“…formation, [14][15][16][17] and the formation of fully mature megakaryterized by bone marrow megakaryocyte hyperplasia and clusocytes and functional platelets in liquid culture. 18 Injections of ters of megakaryocytes, in which many of the megakaryocytes recombinant TPO into mice and nonhuman primates increase are atypical.…”
Section: Agnogenic Myeloid Metaplasia (Amm) Is a Disease Charac-mentioning
confidence: 99%
“…formation, [14][15][16][17] and the formation of fully mature megakaryterized by bone marrow megakaryocyte hyperplasia and clusocytes and functional platelets in liquid culture. 18 Injections of ters of megakaryocytes, in which many of the megakaryocytes recombinant TPO into mice and nonhuman primates increase are atypical.…”
Section: Agnogenic Myeloid Metaplasia (Amm) Is a Disease Charac-mentioning
confidence: 99%
“…Recently, several groups [2][3][4][5] cloned the ligand for the c-Mpl proto-oncogene [6] which is a member of the cytokine receptor superfamily. These studies and others have demonstrated that c-Mpl ligand plays a critical role in megakaryocytopoiesis and thrombopoiesis both in vitro and in vivo [2][3][4][5][7][8][9][10]. Therefore, c-Mpl ligand has been termed thrombopoietin (TPO) [3,7,8] or megakaryocyte growth and development factor (MGDF) [4].…”
Section: Introductionmentioning
confidence: 99%
“…These studies and others have demonstrated that c-Mpl ligand plays a critical role in megakaryocytopoiesis and thrombopoiesis both in vitro and in vivo [2][3][4][5][7][8][9][10]. Therefore, c-Mpl ligand has been termed thrombopoietin (TPO) [3,7,8] or megakaryocyte growth and development factor (MGDF) [4]. The cytokine receptor superfamily, which lacks a tyrosine kinase domain, couples ligand binding with the induction of protein-tyrosine phosphorylation that is essential for cytokine signaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The recently defined ligand for the Mpl receptor, thrombopoietin (TPO), has been found to be the principal regulatory cytokine of megakaryocytopoiesis and thrombopoiesis. [4][5][6][7][8] It appears that TPO is able not only to induce differentiation of megakaryocytic precursors, but also to expand early megakaryocytic progenitors. 9,10 TPO also directly affects more primitive hematopoietic cells, not yet committed towards the megakaryocytic lineage.…”
Section: Introductionmentioning
confidence: 99%